Parole Board decision-making: two key challenges for the Parole Board of England and Wales - Saunders, S; Roberts, J (Sweet and Maxwell, 2019)
Discusses, with reference to case law, the challenges of Parole Board decision-making. Examines the difficulties of performing an inquisitorial function within an adversarial system, and applying inconsistent tests for release. Considers the Board's powers and duties, and whether a burden and standard of proof exist within the tests. Notes the need for clear and consistent direction by the courts on the Board's performance of its duties.